Interventions to improve recruitment and retention in clinical trials: a survey and workshop to assess current practice and future priorities - Bower, Peter; Brueton, Valerie; Gamble, Carrol; Treweek, Shaun; Smith, Catrin Tudur; Young, Bridget; Williamson, Paula (Trials, 2014)
Despite significant investment in infrastructure many trials continue to face challenges in recruitment and retention. We argue that insufficient focus has been placed on the development and testing of recruitment and retention interventions. In this current paper, we summarize existing reviews about interventions to improve recruitment and retention. We report survey data from Clinical Trials Units in the United Kingdom to indicate the range of interventions used by these units to encourage recruitment and retention. We present the views of participants in a recent workshop and a priority list of recruitment interventions for evaluation (determined by voting among workshop participants). We also discuss wider issues concerning the testing of recruitment interventions. Methods used to encourage recruitment and retention were categorized as: patient contact, patient convenience, support for recruiters, monitoring and systems, incentives, design, resources, and human factors. Interventions felt to merit investigation by respondents fell into three categories: training site staff, communication with patients, and incentives. Significant resources continue to be invested into clinical trials and other high quality studies, but recruitment remains a significant challenge. Adoption of innovative methods to develop, test, and implement recruitment interventions are required.